Does the insurance sector really matter for economic growth? Evidence from Central and Eastern European countries - Bayar, Yilmaz; Dan Gavriletea, Marius; Danuletiu, Dan Constantin (Journal of Business Economics and Management, 2021)
This paper analyses the impact of insurance sector development on economic growth based on a sample that includes 14 Central and Eastern European (CEE) post-transition countries for a period of 19 years, from 1998 to 2016. Considering the presence of cross-section dependence and multiple structural breaks, recently developed panel econometric techniques were employed and led to the following conclusions: (1) life insurance has no significant effect on economic growth in both panel and individual countries, (2) non-life insurance positively affects economic growth in both panel and individual countries, (3) Dumitrescu and Hurlin causality test indicates a unidirectional causality running from economic growth to both life and non-life insurance and infers the absence of causal connection between life and non-life insurance and economic growth.